2011
DOI: 10.2202/1446-9022.1262
|View full text |Cite
|
Sign up to set email alerts
|

Compatibility with Firm Dominance

Abstract: This paper analyzes the effect of firm dominance on the incentives to become compatible and how compatibility decisions affect investment incentives. We will consider compatibility in two dimensions: compatibility of the complementary good and inter-network compatibility. We show that if products are substitutes, compatibility tends to be welfare decreasing with the potential negative consequences of increasing compatibility being more likely when asymmetries are strong. We also find that in many instances the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Our contribution is also related to prior research work on competition between two platforms with different standalone value or between firms with different installed base and compatibility (Adner, Chen, & Zhu, 2020;Casadesus-Masanell & Ruiz-Aliseda, 2008;J. Chen, Doraszelski, & Harrington, 2009;Cremer & Thisse, 1991;Doganoglu & Wright, 2006;Farrell & Klemperer, 2007;Malueg & Schwartz, 2006;Maruyama & Zennyo, 2013;Viecens, 2011). We derive some novel results by focusing on studying platforms' incentives for data and information sharing.…”
Section: Platformmentioning
confidence: 98%
“…Our contribution is also related to prior research work on competition between two platforms with different standalone value or between firms with different installed base and compatibility (Adner, Chen, & Zhu, 2020;Casadesus-Masanell & Ruiz-Aliseda, 2008;J. Chen, Doraszelski, & Harrington, 2009;Cremer & Thisse, 1991;Doganoglu & Wright, 2006;Farrell & Klemperer, 2007;Malueg & Schwartz, 2006;Maruyama & Zennyo, 2013;Viecens, 2011). We derive some novel results by focusing on studying platforms' incentives for data and information sharing.…”
Section: Platformmentioning
confidence: 98%
“…Maruyama and Zennyo found that compatibility depended on product lifecycles; once most users have purchased hardware, platform firms' profits accrue largely from content purchases, whereupon competing platform firms have incentives to become compatible [21]. Casadesus-Masanell and Ruiz-Aliseda, for example, explained large platform firms' preference for incompatibility in terms of the quest for market dominance [22], and Viecens showed that compatibility will always be preferred by a platform firm with smaller standalone value and never by its competitor [23]. Several studies in this literature examined compatibility incentives where one firm has a larger installed base (e.g., [24], [25], [26] and [27]) and found that it is less willing to be compatible because, with compatibility, it has to share its network, while with incompatibility, it can maintain its market dominance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The few studies that examine asymmetric platforms typically find weak platforms to seek compatibility in order to steal market share from stronger platforms, and stronger platforms to have no incentive to establish compatibility. Casadesus-Masanell and Ruiz-Aliseda (2009), for example, explain large platforms' preference for incompatibility in terms of the quest for market dominance, and Viecens (2011) shows that compatibility will always be preferred by a platform with smaller standalone value and never by its competitor. Dou (2014) finds, in a model with vertically differentiated platforms and content, that when an inferior platform owns premium content, it is optimal for the inferior platform to offer such content to a superior platform.…”
Section: Literature Reviewmentioning
confidence: 99%